Specific toxicity in six rodent species from China of a new modified norbormide. Issue 4 (2nd October 2019) - Ma, Xi; Hopkins, Brian; Gao, Xincheng; Feng, Zhiyong; Wang, Deng
ABSTRACT: Norbormide (NRB) is a Rattus -specific toxicant that has low palatability and produces sub-lethal dosing in the field, thereby limiting its effectiveness as a rodent control tool. In this study, we assessed the species-specific effect and time to death of a lethal dose of a fatty acid derived pro-toxicant of NRB, named DR8, in six rodent species from China; three species of Rattus and three non- Rattus species. Our results showed three species/subspecies of Rattus were sensitive to DR8, with LD50 values being less than 50 mg/kg, while non- Rattus rodent species were totally insensitive to this drug. As expected, the time to death in the three species of Rattus was longer in those rats dosed with DR8 compared to those dosed with NRB. This indicated that DR8 possesses a slower activity profile to NRB, and therefore supports its potential to increase palatability and be a promising species-specific tool for rodent pest management. LSID  zoobank.org:pub:37372DC5-588E-4F39-8C25-A7A84AD7FE57